Sunbathing for Hospitalized Patients: A humanized strategy (Research, Society and Development, 2022)
The physical environment can be responsible for the development of psychological disorders, disorientation and sleep deprivation. Added to this are the implications resulting from hospitalization, among which we highlight the removal of the patient from living at home, from daily leisure and work activities, and the introduction of new habits, directly influencing mental health. Sunbathing therapy, characterized by exposure to sunlight, in addition to alleviating the emotional effects resulting from the hospitalization process, contributes to the maintenance of serum levels of vitamin D, responsible for insulin metabolism, regulation of mineral metabolism and of the immune, cardiovascular and musculoskeletal systems, and in the serum levels of melatonin and serotonin, thus favoring an improvement in mood. In this perspective, the general objective is to reflect on the benefits of sunbathing for hospitalized patients. This is a descriptive, qualitative and reflective study. It was observed that the strategies of Humanization in Health are essential for the rehabilitation and recovery of hospitalized patients. The literature confirms positive repercussions on physical and psychological health through the regular practice of sunbathing. Sun exposure reduces the psychological effects of prolonged hospitalization and prevents numerous diseases. It is concluded that the Sunbathing routine is a light care technology, humanized, and important for treatment adherence. It is relevant to disseminate knowledge about this. humanization strategy for the promotion of well-being.